Effect of 1,25-Dihydroxyvitamin D(3) on the Renal Handling of P(i) in Thyroparathyroidectomized Rats - Bonjour, J-P. (1977)
The kidney adapts its tubular capacity to transport inorganic phosphate (P(i)) according to the dietary supply of P(i) in both intact and thyropara-thyroidectomized (TPTX) rats. However, in TPTX rats the capability of the renal tubule to adapt to a high P(i) diet is diminished. In TPTX rats the production of the active vitamin D(3) metabolite, 1,25-dihydroxyvitamin D(3) [1,25-(OH)(2)D(3)], is also reduced. 1,25-(OH)(2)D(3) has been shown to have a marked effect on P(i) metabolism. Therefore the question arises whether the deficient production of 1,25-(OH)(2)D(3) contributes to the alteration of the tubular transport of P(i) observed in chronically TPTX rats. In the present investigation, vitamin D-replete rats were sham operated (SHAM) or thyroparathyroidectomized and then pair fed diets containing either 0.2 or 1.2 g/100 g P for 7 days. During this period, groups of SHAM and TPTX rats received i.p. 2 × 13 pmol/day of 1,25-(OH)(2)D(3), a dose which was shown to just normalize the decreased intestinal absorption of Ca and P(i) in TPTX rats. The capacity of tubular P(i) transport was then assessed by measuring the fractional excretion of P(i) (FEP(i)) at increasing plasma P(i) concentration ([P(i)](Pl)) obtained by acute infusion of P(i). The results show that in SHAM rats fed either P diet, 1,25-(OH)(2)D(3) has no effect on the renal handling of P(i). In TPTX rats fed 1.2 g/100 g P diet, 1,25-(OH)(2)D(3) increases FEP(i) over a wide range of [P(i)](Pl.) In TPTX rats fed a 0.2 g/100 g P diet, 1,25-(OH)(2)D(3) does not alter FEP(i) up to a [P(i)](Pl) of 3.0-3.5 mM, but does increase it at higher [P(i)](Pl.) In fact, on both diets TPTX rats supplemented with 1,25-(OH)(2)D(3) appear to have the same renal handling of P(i) as SHAM counterparts. The effect of 1,25-(OH)(2)D(3) was not associated with a change in urine pH or in urinary excretion of cyclic AMP and was maintained under marked extracellular volume expansion. It was associated with a rise in plasma calcium in the TPTX rats fed the high, but not the low, P diet. In TPTX rats fed 1.2 g/100 g P diet, 25-hydroxyvitamin D(3) in doses of 2 × 130 or 2 × 1,300 pmol/day i.p. did not increase FEP(i.) In conclusion, 1,25-(OH)(2)D(3) administered in physiological amounts to TPTX rats restores to normal the capability of the renal tubule to excrete P(i) and to adapt to large variation in dietary P(i). The results suggest that 1,25-(OH)(2)D(3) plays an important role in the regulation of the renal handling of P(i) and that the chronic change in the tubular capacity to transport P(i) after TPTX may be due to the decreased formation of 1,25-(OH)(2)D(3).